Self-assembled mycolic acid antigens on gold electrode as an impedimetric immunosensing platform for active tuberculosis - Ozoemena, Kenneth I. (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2009.